2012
DOI: 10.1021/nn302954n
|View full text |Cite
|
Sign up to set email alerts
|

Growth of In Situ Functionalized Luminescent Silver Nanoclusters by Direct Reduction and Size Focusing

Abstract: We have used one phase growth reaction to prepare a series of silver nanoparticles (NPs) and luminescent nanoclusters (NCs) using sodium borohydride (NaBH(4)) reduction of silver nitrate in the presence of molecular scale ligands made of polyethylene glycol (PEG) appended with lipoic acid (LA) groups at one end and reactive (-COOH/-NH(2)) or inert (-OCH(3)) functional groups at the other end. The PEG segment in the ligand promotes solubility in a variety of solvents including water, while LAs provide multident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
125
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 124 publications
(127 citation statements)
references
References 89 publications
2
125
0
Order By: Relevance
“…However, the reported etching methods to obtain Au and Ag NCs always involve toxic organic solvents, rigorous reaction conditions (for example, oxygen-free and high temperature) and complicated procedures. [13][14][15] Among numerous studies on metal nanoclusters, the aggregation behavior of small nanoparticles has attracted widespread attention in recent years, including aggregation-induced optical property changes and their applications, the effects of aggregation on biocompatibility and toxicity, and the shaping of nanocluster supracrystals by controlling the aggregation process. [16][17][18][19] Agglomeration-induced emission (AIE) of fluorescent metal nanoclusters, usually triggered by inorganic ions or special solvents, is becoming an important research focus, [20][21][22] and the reversible AIE of the nanoclusters has drawn the interest of researchers.…”
Section: Introductionmentioning
confidence: 99%
“…However, the reported etching methods to obtain Au and Ag NCs always involve toxic organic solvents, rigorous reaction conditions (for example, oxygen-free and high temperature) and complicated procedures. [13][14][15] Among numerous studies on metal nanoclusters, the aggregation behavior of small nanoparticles has attracted widespread attention in recent years, including aggregation-induced optical property changes and their applications, the effects of aggregation on biocompatibility and toxicity, and the shaping of nanocluster supracrystals by controlling the aggregation process. [16][17][18][19] Agglomeration-induced emission (AIE) of fluorescent metal nanoclusters, usually triggered by inorganic ions or special solvents, is becoming an important research focus, [20][21][22] and the reversible AIE of the nanoclusters has drawn the interest of researchers.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it may be concluded that the PL at 530 nm originates from Ag-P3HT and not from thermal degradation of P3HT or Ag NPs. Some research groups reported silver nanoclusters with diameters smaller than 2 nm are luminescent and their fluorescence maximum resides around 680 nm [16,23,24]. Since it was not observed in the PL spectra, we conclude that the luminescent Ag nanoclusters were not formed.…”
Section: Chemical Binding In Ag-p3ht Characterized By 1 H Nmr Ftir Amentioning
confidence: 59%
“…Longer conjugation length in the polymer backbone results in a smaller I sym /I asym ratio. While the ratio is only 2 for pristine P3HT [16], it is 10.34 for Ag-P3HT, which suggests the conjugation length is decreased in the chemically-linked Ag-P3HT nanocomposite. The conjugation length is related to the luminescent properties of P3HT derivatives [20].…”
Section: Chemical Binding In Ag-p3ht Characterized By 1 H Nmr Ftir Amentioning
confidence: 95%
See 2 more Smart Citations